Frequency shifting of ring filter using lumped capacitors / Norashikin Norddin - Norddin, Norashikin (2010)
Frequency shifting of ring filter is designed by adding four lumped capacitors to its initial topology. The capacitors value used is 8.2pF. The purpose of the capacitors used in this design is to shift the center frequency of the initial filter to lower frequency and result in a smaller filter as compared to the one realized directly at the desired frequency. The filter is realized FR4 substrate with a relative dielectric constant of 5.4, thickness of 1.6 mm and loss tangent of 0.02. The layout, simulation and measurement result are presented in this paper.